Application of natural antioxidant extract from guava leaves (Psidium guajava L.) in fresh pork sausage. (July 2020) - Tran, Thi Thu Tra; Ton, Nu Minh Nguyet; Nguyen, Thanh Triet; Le, Van Viet Man; Sajeev, Dishnu; Schilling, M. Wes; Dinh, Thu T.N.
Abstract: The current study was conducted to determine the antioxidant efficacy of guava leaf extract (3000 to 6000 ppm on fat basis) in fresh pork sausage, compared with negative control (CON) and 200 ppm butylated hydroxytoluene (BHT), for 0, 1, 4, 7, 10, and 14 d at 4 °C. The extract provided a total antioxidant capacity of 1505 μmol trolox equivalence/g. From d 4, the extract at 5000 and 6000 ppm provided greater ( P  < .05) antioxidant capacity than the CON and was either similar ( P  > .05) or greater ( P  < .05) than BHT. From d 4, the sausage formulated with 4000 to 6000 ppm of guava leaf extract had less conjugated dienes, lower peroxide and acidic values, less thiobarbituric reactive substances value, and better color ( P  < .05) than the CON and did not differ from BHT ( P  > .05). Guava leaf extract at 4000 ppm or greater is effective in preventing oxidation in fresh pork sausage. Highlights: Guava leaf extract (GLE) prevented oxidation in fresh pork sausage GLE at concentrations of 5000 and 6000 ppm on a fat basis gave similar protection against lipid oxidation as 200 ppm BHT Use of 4000 ppm GLE on a fat basis provided optimum protection against discoloration